Implementation of the 10 Quality Pillars in the Management of Qur’an Learning at Ummi Foundation - Muhammad Ruslan; Abd Rahman; Suraiya Chapakiya (MASI Mandiri Edukasi, 2025)
The quality of Al-Qur’anic education in many institutions often struggles to maintain consistency, both in methodology and management. To address these challenges, this study explores the implementation of the 10 Quality Pillars in managing Qur’anic learning through the Ummi Method. The aim is to assess the effectiveness of each pillar in enhancing students’ recitation accuracy and memorization skills. This research employs a descriptive qualitative approach, utilizing observation, interviews, and document analysis within Qur’anic education institutions, applying the Ummi Method. Data were analyzed thematically, focusing on the consistency of quality assurance practices. Findings reveal that management support, well-structured learning schedules, an ideal teacher-to-student ratio, effective coordinators, and clearly defined targets play a critical role in sustaining quality standards. Systematic learning stages, the application of mastery learning, internal and external supervision, and regular student progress reports significantly reduce recitation errors, strengthen tajwid proficiency, and enhance parental and community trust in the institution. The study concludes that the consistent application of the 10 Quality Pillars serves as an effective strategy for developing a structured and sustainable Qur’anic learning system. These findings offer practical insights for Islamic educational institutions seeking to improve the management and delivery of Qur’anic education through standardized quality measures.